1996
DOI: 10.1525/si.1996.19.1.21
|View full text |Cite
|
Sign up to set email alerts
|

National Hatred, Female Subjectivity, and the Boundaries of Cultural Discourse

Abstract: In light of a study in Israel, which found that 28% of secular girls and 63% of religious girls expressed strong hatred toward Arabs (Cal and Maislees 1989), this paper explores the difference in emotional experience between the two groups of girls. Through in‐depth interviews, it examines the meaning of national hatred as knowledge produced within a particular cultural discourse. In the case of the religious girls, feelings of hatred are produced through defensive emotion work aimed at securing the position o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Niza Yanay (1995Yanay ( , 1996Yanay ( , 2002 coded 200 letters sent to targets of hate (Tempkin and Yanay, 1989) to look at strategies perpetrators used to express themselves and admonish their objects of hatred. In this research, Temkin and Yanay found that the haters commonly wrote about their desire to exclude the members of the Israeli Zionist party from the larger collective of Israel and Jewish identity all together.…”
Section: Niza Yanay and Hate Lettersmentioning
confidence: 99%
“…Niza Yanay (1995Yanay ( , 1996Yanay ( , 2002 coded 200 letters sent to targets of hate (Tempkin and Yanay, 1989) to look at strategies perpetrators used to express themselves and admonish their objects of hatred. In this research, Temkin and Yanay found that the haters commonly wrote about their desire to exclude the members of the Israeli Zionist party from the larger collective of Israel and Jewish identity all together.…”
Section: Niza Yanay and Hate Lettersmentioning
confidence: 99%
“…In another study (Yanay, 1996), I demonstrated the interplay between types of national discourse (secular and religious), emotional experience (of hatred), and the construction of (women's) subjectivity. This was based on in-depth interviews with nearly 50 Jewish adolescent girls, half of them secular (found in survey research to have the lowest rates of hatred towards Arabs), and half belonging to the national religious movement (found in survey research to have the highest rates of hatred toward Arabs).…”
mentioning
confidence: 97%
“…This article explores this fantasmatic "conversion offer" in order to demonstrate the hidden workings of collective hatred and its ambivalent mechanisms. Based on previous work (Yanay, 1989(Yanay, , 1995(Yanay, , 1996, this article claims that collective hatred signifies a failure to mediate between similarity and difference, closeness and separation, isolation and connectedness, at the same time that national and religious groups aspire to be included and be recognized as part of humanity.Since the September 11 attacks on the World Trade Center and the Pentagon, hatred has become very topical. The concept has been circulated from the White House and the media to our streets, homes, and hearts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 22 Pertinent in this regard is Niza Yanay's study of secular and religious girls' feelings towards Arabs in which she suggests that ‘two main motifs dominate the [religious] girls’ expressions of fear and hate: the street as a place of danger and the body as the locus of injury' (Yanay 1996: 29). …”
mentioning
confidence: 99%